Heat Exchange between Thermometer Well and Pipe Wall in Natural Gas Metering Systems - Roman Fedoryshyn; Fedir Matiko (Energy Engineering and Control Systems)
This paper deals with the accuracy of gas flow temperature measurement in natural gas metering systems. The effect of heat exchange between thermometer well and the pipe wall on the accuracy of gas flow temperature measurement is investigated. A mathematical model is proposed to calculate the additional systematic error of gas flow temperature measurement caused by heat exchange between thermometer well and the pipe wall. Calculation results were compared to the corresponding experimental values of this error. The maximum relative deviation of calculation results from experimental values does not exceed 6 %. The effect of gas flow temperature measurement error on the accuracy of gas flow rate and volume measurement is analyzed. Measures are proposed to minimize the additional systematic error of gas flow temperature measurement and to improve the accuracy of natural gas metering.